1984
DOI: 10.1017/s0317167100045935
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Head Trauma on Society

Abstract: In this address I shall discuss head trauma from an angle which may be unusual for neuroscientists. Our preoccupations are diagnostic challenges and management problems, but that which we experience at the bedside is only a narrow segment of a continuum which started with trauma somewhere in a war, on the road, at home, on the football field, in the boxing ring, and in many other distinct locations. When our role is over, there are only three places where head trauma victims can be found; in cemeteries, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

1988
1988
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Nosso estágio de desenvolvimento nos coloca entre extremos, como por exemplo, Canadá -Uganda; por isso, temos etiologias comuns a estas distintas sociedades. Exemplificando, possuímos prevalência de NC, típica de terceiro mundo 1,9 , combinada com taxas de TCE que excedem em muito ao verificado nos países desenvolvidos 10,11 . Aliás, apesar da nossa fama de produzir bons esportistas (e pilotos também), somos pessimamente mal educados no trânsito.…”
Section: Discussionunclassified
“…Nosso estágio de desenvolvimento nos coloca entre extremos, como por exemplo, Canadá -Uganda; por isso, temos etiologias comuns a estas distintas sociedades. Exemplificando, possuímos prevalência de NC, típica de terceiro mundo 1,9 , combinada com taxas de TCE que excedem em muito ao verificado nos países desenvolvidos 10,11 . Aliás, apesar da nossa fama de produzir bons esportistas (e pilotos também), somos pessimamente mal educados no trânsito.…”
Section: Discussionunclassified
“…Regardless of the cause, race, sex, or age of the injured, head injuries are often a severe and expensive injury for society, the individual, and the military [8]. Preventive efforts that reduce the morbidity and mortal ity of head injuries could save the military and the afflicted individuals a great deal of money as well as misery.…”
Section: Discussionmentioning
confidence: 99%
“…In reviewing the clinical records of these cases, enough cases of confirmed alco hol involvement occurred to suggest that it is being significantly underreported on the clinical record cover sheet although it was frequently noted in the history. This is not surprising since alcohol has often been asso ciated with head injury [7], One study found that of 159 cases of moderate head injury, 53% were intoxicated and 73% had some alcohol present in their blood [8].…”
Section: Discussionmentioning
confidence: 99%